Food safety assessment and 28-day toxicity study of the synbiotic medical food consortium SBD121 - D. Davidson Easson; Vincent A. Murphy; Alicia E. Ballok; Maria J. Soto-Giron; Kelsey J. Miller; Mark R. Charbonneau; Eric M. Schott; Tracy Greene; Joseph Rodricks; Gerardo V. Toledo (Food and Chemical Toxicology, 2024)

Critical considerations in the review of the toxicological evidence regarding the potential carcinogenicity of aspartame - Robinan Gentry; Tracy Greene; Harvey J. Clewell; Joseph V. Rodricks (Food and Chemical Toxicology, 2023)

Respiratory effects of oral mitragynine and oxycodone in a rodent model - Jack E. Henningfield; Joseph V. Rodricks; Aaron M. Magnuson; Marilyn A. Huestis (Psychopharmacology, 2022)
Rationale Kratom derives from Mitragyna speciosa (Korth.), a tropical tree in the genus Mitragyna (Rubiaceae) that also includes the coffee tree. Kratom leaf powders, tea-like decoctions, and commercial extracts are taken orally, primarily for health and well-being by millions of people globally. Others take kratom to eliminate opioid use for analgesia and manage opioid withdrawal and use disorder. There is debate over the possible respiratory depressant overdose risk of the primary active alkaloid, mitragynine, a partial μ-opioid receptor agonist, that does not signal through ß-arrestin, the primary opioid respiratory depressant pathway. Objectives Compare the respiratory effects of oral mitragynine to oral oxycodone in rats with the study design previously published by US Food and Drug Administration (FDA) scientists for evaluating the respiratory effects of opioids (Xu et al., Toxicol Rep 7:188–197, 2020). Methods Blood gases, observable signs, and mitragynine pharmacokinetics were assessed for 12 h after 20, 40, 80, 240, and 400 mg/kg oral mitragynine isolate and 6.75, 60, and 150 mg/kg oral oxycodone hydrochloride. Findings Oxycodone administration produced significant dose-related respiratory depressant effects and pronounced sedation with one death each at 60 and 150 mg/kg. Mitragynine did not yield significant dose-related respiratory depressant or life-threatening effects. Sedative-like effects, milder than produced by oxycodone, were evident at the highest mitragynine dose. Maximum oxycodone and mitragynine plasma concentrations were dose related. Conclusions Consistent with mitragynine’s pharmacology that includes partial µ-opioid receptor agonism with little recruitment of the respiratory depressant activating β-arrestin pathway, mitragynine produced no evidence of respiratory depression at doses many times higher than known to be taken by humans.

Application of a Key Events Dose-Response Analysis to Nutrients: A Case Study with Vitamin A (Retinol) - A. Catharine Ross; Robert M. Russell; Sanford A. Miller; Ian C. Munro; Joseph V. Rodricks; Elizabeth A. Yetley; Elizabeth Julien* (Critical Reviews in Food Science and Nutrition, 2009)